Pengaruh Konten pada Intensi Konsumen untuk Membeli Produk Kecantikan di Tiktok - Lavina, Gabriella; Mediana, Xecilia; Widjojo, Handyanto; Murniadi, Krishnamurti (Kajian Branding Indonesia, 2024)
TikTok as the fastest growing social media has expanded to the e-commerce industry. Influencer affiliate marketing strategy takes part in their success. The contents of TikTok have these attributes: utilitarianism from their information quality and hedonism from the humor and originality of its creators. Referring to the Stimulus Organism Response (SOR) theory, humor, originality, and quality is a great stimulus to attract responses from the audience. With this research, the writer seeks for an understanding of how attributes persuade the audience’s attitudes and intention to purchase from TikTok as an application. Questionnaires consisting of 5 variables and 23 indicators will be distributed to TikTok users. The data analysis for this study will be conducted using SmartPLS Structural Equation Modeling (SEM). The result indicates that a positive attitude is proven to moderate the relationship between originality, quality and purchase intention. These findings contribute theoretically and practically that might help business owners, influencer affiliates and TikTok in decision making or strategizing.